Efficacy of Split Schedule Versus Conventional Schedule Neoadjuvant Cisplatin‐Based Chemotherapy for Muscle‐Invasive Bladder Cancer. (6th February 2019) - Osterman, Chelsea K.; Babu, Dilip S.; Geynisman, Daniel M.; Lewis, Bianca; Somer, Robert A.; Balar, Arjun V.; Zibelman, Matthew R.; Guancial, Elizabeth A.; Antinori, Gianna; Yu, Shun; Narayan, Vivek; Guzzo, Thomas J.; et al.
Abstract: Neoadjuvant cisplatin‐based chemotherapy (NAC; 70 mg/m 2 ) is standard of care for muscle‐invasive bladder carcinoma (MIBC). Many patients (pts) cannot receive cisplatin because of renal impairment, and administration of cisplatin 35 mg/m 2 on day 1 + 8 or 1 + 2 (i.e., split schedule) is a commonly used alternative. In this retrospective analysis, we compared complete (pT0) and partial (<pT2) pathologic response rates between split schedule (SS) and conventional schedule (CS) pts, after 1:1 matching on chemotherapy regimen, number of cycles, tumor histology, and clinical stage. Eighty matched pts were identified. pT0 rates were 17.5% (95% confidence interval [CI], 7%–33%) and 32.5% (95% CI, 19%–49%) in SS and CS cisplatin pts, respectively ( p  = .21), corresponding to an odds ratio for pT0 of 0.45 (95% CI, 0.16–1.31) with SS cisplatin. Split schedule cisplatin was associated with numerically but not statistically significant lower pathologic response rates relative to full dose. Abstract : Neoadjuvant cisplatin‐based chemotherapy followed by radical cystectomy is the current standard of care for patients with muscle‐invasive urothelial carcinoma of the bladder. This article evaluates the use of a split schedule cisplatin‐based chemotherapy for bladder cancer treatment.